The Five Elements of Professional Networking. - Lee, Christopher K. (Morgan James Publishing, 2025)
Networking.For many people, the word conjures up images of stuffy events--shaking hands, making small talk, and exchanging business cards.To them, "networking" feels forced, awkward, even disingenuous.It doesn't have to be this way.True networking is more than attending events and trading favors.